A review: intelligent controllers for tropical food storage system - Adeyinka Abdulquadri, Oluwo; Salami, Momoh Jimoh Emiyoka; Md. Raisuddin, Khan; Aibinu, Abiodun Musa (2011)
Food security can be assured by improving on post harvest storage methods. Food stored under improper storage conditions are prone to increased respiration and transpiration processes which often result in depletion and weight loss of edible material. Storage temperature and relative humidity are major factors that ultimately determine product quality and quantity. This paper presents a survey on methods of post harvest storage systems. The indigenous methods of tropical food storage common to the West African region are discussed. The attendant problems associated with these methods are highlighted. Intelligent control methods are also discussed. A novel intelligent controller is proposed to sustain product quality and quantity by optimizing the storage process.